HIP 13962 – THE POSSIBLE FORMER MEMBER OF BINARY SYSTEM WITH SUPERNOVA - Yushchenko, V.; Yushchenko, A.; Gopka, V.; Shavrina, A.; Kovtyukh, V.; Hong, K. S.; Mkrtichian, D.; A-Thano, N. (Одеські астрономічні публікації, 2016)
The run away supergiant star HIP13962 (spectral type G0Ia) was recently pointed as a possible former binary companion of young pulsar PSRJ0826+2637. The spectraof HIP13962 wereo btained in Haute-Provence observatory (France), in Bohuynsan observatory (Korea), and also in NARIT (Thailand) with1.9, 1.8, and 2.4 meter telescopes respectively. The spectra were obtained in 1995, 2003, 2005, 2014, and 2015. Signiﬁcant variations of the spectrum are detected. The cores of strong lines show complicated structure, the brightness of the star is variable. The cycles of photometric variations have been changed. We analyzed the spectral observations and present the preliminarychemical composition for elements from iron to lead. The abundance pattern cannot be ﬁtted by solar system r&s process abundance distribution.